Simulation for the estimation of the survival probabilities of enterprises and banks within a prolonged duration of the debt crisis - Costas Kyritsis; Evangelos Hytis (Proceedings of the 3rd International Conference on Quantitative and Qualitative Methodologies in the Economic and Administrative Sciences, 23-24 May 2013, 2013)
In the current paper, we study the stability and the survival probabilities of enterprises and banks within a prolonged duration of the debt-crisis, with Monte Carlo simulation. We utilize historical data from banks and enterprises within the debt-crisis to define crisis-variability and crisis-average values of input parameters of the simulation. We introduce the concept of equities maximum draw-down as dynamic survival indicator. Finally we estimate the survival probabilities of enterprises and banks within a prolonged duration of the debt crisis.
Keywords: C63; C53; C8; G2; M41; 330; Monte Carlo simulation; Bankruptcy probabilities; Debt-crisis; Bank stability